Intelligent material handling machines - Telek, Péter (Advanced Logistic Systems - Theory and Practice, 2024)
Automatic material handling is basically used to implement the automatic movement of goods, but due to today's expectations, this technically requires high-level computer control of various sensing, control, and monitoring tasks. Due to flexible service needs, these tasks require dynamic implementation, which may require the use of intelligent solutions. In this article, I will review the interpretation and role of intelligent material handling in modern service systems, and outline the concept and levels of intelligent material handling machines in terms of different device versions. In addition, I will present the intelligent solutions and their application areas encountered in logistics activities today through examples.